Referendum Authorization Procedures in Europe A Comparative Analysis - Forgács, Anna (Edward Elgar Publishing, 2023)
Exploring the referendum practices of eight European states, this book unpacks the intricacies of the institutional and procedural settings of referendum authorization to reach an equilibrium between the exercise of popular sovereignty and the protection of rule of law. The book also examines how, by authorizing certain issues and refusing others, state institutions can exercise considerable control over the whole referendum process.